Rewriting Maimonides: early commentaries on the Guide of the Perplexed - De Souza, Igor H. (Jewish thought, philosophy, and religion, 2018)
Intro -- Acknowledgments -- Contents -- Abbreviations -- 1. Commentaries on the Guide of the Perplexed: A Brief History -- 2. Philosophical Commentators of the Guide, 13th-14th Centuries -- 3. Moses ben Solomon of Salerno: Hebrew-English Text -- 4. Shem Tov ben Joseph ibn Falaquera: English Text -- 5. Zeraḥiah ben Isaac ben Sheʼaltiʼel Ḥen: Hebrew-English Text -- 6. Joseph ben Abba Mari ibn Kaspi: Hebrew-English Text -- 7. Moses ben Joshua ben David of Narbonne: Hebrew-English Text -- 8. Commentaries on the Guide: A Synthetic Conclusion -- Bibliography -- Subject Index -- Persons Keywords Index -- Index for chapters of the Guide.